Publikasi Ilmiah untuk Akselerasi Kenaikan Pangkat Guru Bahasa Inggris SMP Negeri Se-Lombok Tengah - Haerazi Haerazi; Lalu Ari Irawan; Arif Rahman; Jupri Jupri; I Ketut Warta (Sasambo: Jurnal Abdimas (Journal of Community Service), 2020)
Publication of scientific papers is a must done by English teachers in Indonesiato promote their level of teachers. Publication of scientific papers is actuallyalso oriented to develop professional teachers because the published works arethose that lead the profession and improvement of the teaching-learningprocess. It can be done through the Classroom Action Research. Thus, thecomponents of instructions that can be done through the CAR include thestudents, teachers, subject matter, learning tools or facilities, learning outcomes,and management. The method of this workshop used Active ParticipatoryAction. The necessity of publication is intended so that teachers can improve thequality of the profession and the quality of learning in their schools. To achievethis goal, training in scientific writing was carried out by Lecturer Teams fromUNDIKMA in collaboration with the Central Lombok District Office. There are13 English teachers successfully publish their writings in national accreditedjournals.